Micro Medium and Small aEnterprise Human Resources’ Creativity in West Java Through Intellectual Property Rights (IPR) License in the Pandemic Covid-19 Situation (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The creativity of human resources at Micro, Medium and Small Enterprise (MSME) had an essential part for the development of MSME in recent Covid-19 pandemic situation. The matter of creativity was significantly required through an intellectual property rights (IPR) license agreement support; furthermore, resulted the optimization of economic as its exclusive right equitably protected. Regardless the license agreement owned by West Java MSMEs was inadequately appropriate. This study purposed to find out how the human resources creativity of West Java MSME and human resources creativity through intellectual property rights license agreement in in the Covid-19 situation. This study applied a cross sectional method, qualitative normative juridical and legal interpretation methods. The descriptive research specification was quantitative analysis, implementing purposive sampling technique to obtain thirty MSME respondents specifically in West Java. In addition, the data collection engaged literature study techniques. The results showed that the creativity of human resource at MSME might increase the demand for MSME products. The human resources creativity including person, process, press and product perspectives were fundamental in the development of MSME. It referred to an indication by the frequency of respondents in carrying out each perspective assessed as a necessity in developing MSME. Thus, intellectual property rights license agreement led to be required aspect in improving, protecting and developing the creativity of human resources, especially during the Covid-19 pandemic situation. It was proven by being understood and trusted by West Java MSME; nevertheless, the participation at the time of socialization was not optimal. In the other hand, West Java MSME had been propertied by the intellectual property rights license agreement. It related to procedural constraints, lack of information and also costs.